2021
DOI: 10.1038/s41467-021-27439-6
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of the mammoth-steppe in central Yukon as revealed by ancient environmental DNA

Abstract: The temporal and spatial coarseness of megafaunal fossil records complicates attempts to to disentangle the relative impacts of climate change, ecosystem restructuring, and human activities associated with the Late Quaternary extinctions. Advances in the extraction and identification of ancient DNA that was shed into the environment and preserved for millennia in sediment now provides a way to augment discontinuous palaeontological assemblages. Here, we present a 30,000-year sedimentary ancient DNA (sedaDNA) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 177 publications
(347 reference statements)
4
78
0
Order By: Relevance
“…Physical anthropologists, forensic practitioners, and historical epidemiologists often obtain valuable data from materials that do not meet the standards of clinical diagnosis. Most nucleic acid recovery from non-optimal and ancient materials has been DNA [19]. However, the recovery of RNA sequences from the 1918-1919 influenza via paraffin sections and victims exhumed from permafrost graves [20] and HIV from lymph node embeds from 1960s [21] shows that RNA under at least some circumstances is more stable than often assumed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical anthropologists, forensic practitioners, and historical epidemiologists often obtain valuable data from materials that do not meet the standards of clinical diagnosis. Most nucleic acid recovery from non-optimal and ancient materials has been DNA [19]. However, the recovery of RNA sequences from the 1918-1919 influenza via paraffin sections and victims exhumed from permafrost graves [20] and HIV from lymph node embeds from 1960s [21] shows that RNA under at least some circumstances is more stable than often assumed.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to records of individuals, related approaches would be valuable if applied to wastewater [24, 25] and eco-environmental contexts. Archived biological diaries from multiple levels would add rich information to retrospective reviews aimed at improving pandemic response [26], public health more generally[27] and enhancing understanding of our relentlessly evolving world[19, 28, 29].…”
Section: Resultsmentioning
confidence: 99%
“…Second, bone frequency may carry a complex relationship to megafaunal population abundance, given the vagaries of collection efforts and given that past environmental change may alter the likelihood of bone preservation. This study also does not leverage some of the newer proxies for megafaunal presence and function, including coprophilous fungal spore records ( 20 ) and ancient sedimentary DNA ( 21 ). Ancient DNA records hint at the persistence of at least small populations of mammoth and horse from the central Yukon as late as 6,000 y ago, long after the apparent disappearance of these animals from the bone record ( 21 ).…”
Section: Implications For Contemporary Biodiversity Managementmentioning
confidence: 99%
“…This study also does not leverage some of the newer proxies for megafaunal presence and function, including coprophilous fungal spore records ( 20 ) and ancient sedimentary DNA ( 21 ). Ancient DNA records hint at the persistence of at least small populations of mammoth and horse from the central Yukon as late as 6,000 y ago, long after the apparent disappearance of these animals from the bone record ( 21 ). These critiques are not serious—the Monteath et al.…”
Section: Implications For Contemporary Biodiversity Managementmentioning
confidence: 99%
“…Terrestrial ecosystems have lost a significant proportion of their megafauna (species > 44.5 kg) (Stuart 2015; Malhi et al 2016; Smith et al 2016; Smith and Lyons 2011; Smith et al 2018), with many of these extinctions occurring during the Late Pleistocene due to anthropogenic pressures (Smith et al 2019; Sandom et al 2014; Barnosky et al 2004) and climate change (Barnosky et al 2004; Mann et al 2019; Monteath et al 2021; Wang, Zhang, and Kong 2021). Studies have shown that such dramatic extinctions of megafauna have had long-lasting effects on forest structure (Malhi et al 2016; Doughty, Faurby, and Svenning 2016), plant geographic ranges (Doughty et al 2016; Janzen and Martin 1982; Blake et al 2009; Beaune et al 2013), carbon storage (Doughty et al 2016), maintenance of high latitude grasslands (Murchie et al 2021; Zimov et al 2015; Bakker et al 2016), nutrient cycling (Doughty 2017; Wolf, Doughty, and Malhi 2013; Doughty et al 2016; Doughty, Wolf, and Malhi 2013), the perceived host specificity of parasites (Farrell et al 2021) and emergent zoonotic diseases (Doughty et al 2020). Additionally, the life-history traits of the megafauna are not yet classified, limiting our understanding of these big species and the accuracy of studies modelling their impact.…”
Section: Introductionmentioning
confidence: 99%